Rom, Italien. Eugen Petersen und die Fotografie am DAI Rom vor der Gründung der Fotothek. Die Arbeiten des Jahres 2020 für das Projekt »Die römische Fotothek – Visualisierung in den Altertumswissenschaften« - de Luca, Sabina (e-Forschungsberichte des DAI, 2021)
The project investigates the fund of Eugen Petersen, director of the Roman Department from 1887 to 1905, focusing on his role in the establishment of the local photographic collection. 860 letters in the Roman Archives provide an important insight into the workings of the collection prior to the foundation of the Photo Archives, including scholars’ access to photographs and their use of the photographic medium. To elaborate these dynamics with a concrete example, this brief paper discusses the correspondence between Petersen and the classical archaeologist August Mau, which clarifies the organization behind the collecting of negatives for the Institute by his members and the ongoing discussion about the use of photographs in archaeological publications.